The Human Resource Management Study: Correlation of Job Satisfaction and Employee’s Turnover Intention - Fera Indria (Prosiding Amal Insani Foundation, 2024)
Human resources are seen as an important company asset, because humans are a dynamic resource and are always needed in every process of producing goods and services, so to create capable human resource management, companies must pay attention to job satisfaction so that turnover intention problems do not interfere with productivity. company. This is the biggest challenge for companies today, namely how to maintain, maintain and suppress employee turnover intentions. The aim of this research is to determine the relationship between job satisfaction and employee turnover intentions. This research is quantitative research with a correlational approach with a Likert scale measuring scale. The sample consisted of 103 people who were determined using snowball sampling techniques or also known as saturated samples. Data obtained from respondents was processed using simple linear regression data analysis. The research results show that there is a relationship between job satisfaction and employee turnover intentions, it is known that the F value is 76.641 with an effective contribution of 43.1% while the remaining 56.9% is influenced by other factors not examined in this research. The research results provide attention to human resource management studies so that every organization can pay attention to job satisfaction felt by employees in order to reduce or even avoid high turnover intentions.